Response of the wood-decay fungus Schizophyllum commune to co-occurring microorganisms - Krause, Katrin; Jung, Elke-Martina; Lindner, Julia; Hardiman, Imam; Poetschner, Jessica; Madhavan, Soumya; Matthaeus, Christian; Kai, Marco; Menezes, Riya Christina; Popp, Juergen; Svatos, Ales; Kothe, Erika (PLoS ONE, 2020)
Microorganisms are constantly interacting in a given environment by a constant exchange of signaling molecules. In timber, wood-decay fungi will come into contact with other fungi and bacteria. In naturally bleached wood, dark, pigmented lines arising from confrontation of two fungi often hint at such interactions. The metabolites (and pigment) exchange was investigated using the lignicolous basidiomycete Schizophyllum commune, and co-occurring fungi and bacteria inoculated directly on sterilized wood, or on media. In interactions with competitive wood degrading fungi, yeasts or bacteria, different competition strategies and communication types were observed, and stress reactions, as well as competitorinduced enzymes or pigments were analyzed. Melanin, indole, flavonoids and carotenoids were shown to be induced in S. commune interactions. The induced genes included multicopper oxidases lcc1, lcc2, mco1, mco2, mco3 and mco4, possibly involved in both pigment production and lignin degradation typical for wood bleaching by wood-decay fungi.
CRIS-Team Scopus Importer:2023-04-20